Prediksi Pergerakan Harga Saham Menggunakan Support Vector Machines Di Indonesia - Yolanda, Anggie (BUDGETING : Journal of Business, Management and Accounting, 2024)
Predicting stock movements is challenging due to their dynamic nature and influence from various factors. One of these factors is the lack of research considering the use of fundamental analysis regarding currency exchange rates and the use of foreign stock index movements related to technical analysis. This research aims to predict stock price movements in Indonesia based on sentiment analysis, technical analysis, and fundamental analysis using Support Vector Machine. The results obtained have an average prediction accuracy rate of 65.33%. The inclusion of currency exchange rates and foreign stock index movements as predictors in this study can increase the average prediction accuracy rate by 11.78% compared to predictions without using these two variables, which only result in an average prediction accuracy rate of 53.55%. Keywords: Fundamental Analysis, Sentiment Analysis, Stock Prediction, Support Vector Machines, Technical Analysis.